Exercise-Induced Reductive Stress Is a Protective Mechanism against Oxidative Stress in Peripheral Blood Mononuclear Cells. (11th October 2018) - Spanidis, Ypatios; Veskoukis, Aristidis S.; Papanikolaou, Christina; Stagos, Dimitrios; Priftis, Alexandros; Deli, Chariklia K.; Jamurtas, Athanasios Z.; Kouretas, Demetrios
Abstract : Eccentric exercise is a well-studied modality that induces oxidative stress and muscle damage. Furthermore, it promotes inflammatory response in which peripheral blood mononuclear cells (PBMCs) are the major mediators. Although free radicals are necessary in a specific range of concentrations, yet unknown, it remains unclear whether reductive redox status (i.e., increased antioxidant defenses and impaired free radical generation) is beneficial or not. Thus, the aim of the present investigation was to examine the effects of reductive stress and the impact of reduced glutathione (GSH) baseline values on the ability of PBMCs to counteract oxidative stress induced by a potent oxidative agent. PBMCs were isolated from the blood of subjects who performed eccentric exercise and treated with t- BOOH for 24 h. The subjects were clustered in the reductive and the oxidative group on the basis of increased or decreased GSH concentration postexercise compared to preexercise values, respectively. According to our results in PBMCs, lipid peroxidation levels as depicted by thiobarbituric acid reactive substances (TBARS) remained unchanged in the reductive group contrary to the observed enhancement in the oxidative group. In addition, GSH concentration and catalase activity increased in the reductive group, whereas they were not affected in the oxidative group. In conclusion, the effects of an oxidizing agent on the redox status of PBMCs isolated from the blood of athletes after acute eccentric exercise are dependent on the baseline values of GSH in erythrocytes. Otherwise, reductive stress defined by increased GSH levels is a protective mechanism, at least when followed by an oxidative stimulus.